THE DYNAMICS OF THE RECEPTION OF SURAH AL-MULK: AN ANALYSIS OF TRANSMISSION AND TRANSFORMATION IN ISLAMIC LITERATURE - Miftahul Umam (As-Sulthan Journal of Education, 2026)
This research explores the reception, transmission, and transformation of surah al-Mulk in Islamic literature, from hadiths, tafsir, amaliyat, and contemporary works. This study uses the qualitative literature study method, with the application of Hans Robert's theory of Horizon of Expectations and Wolfgang Iser's theory of reception, to analyze the reader's interaction with the text. The findings of this study show that surah al-Mulk is not only seen as a rigid text, but a text that lives with various benefits, both spiritually and materially. The process of transmission occurs through three main patterns: literary quotations, sanad, and discursive traditions that adjust to the dynamics of society. This research shows that the reception of surah al-Mulk has evolved from informative to performative, where the meaning of al-Mulk will be reconstructed based on the spiritual and material needs of readers from various cross-generations.